Implications of including an acknowledgement of parentage clause in the will of parentage clause in the testamentary act - Nuñez Seminario, Ingrid Dayhanna (Revista de Derecho, 2024)
This paper examines the implications of a testator including a testamentary clause that acknowledges parentage. The issue arises due to the fundamentally revocable nature of wills contrasted with the irrevocable character of an acknowledgment of parentage. Key questions include whether such a clause can be revoked as part of a revocable document and when the acknowledgment takes effect—whether upon declaration or only after the testator’s death. The analysis focuses on relevant provisions of the Civil Code, aiming to provide a solution consistent with legal principles and regulatory frameworks.
Keywords: will; parentage; effects; condition; revocability